Dampak Skor Lingkungan, Sosial, dan Tata Kelola (ESG) terhadap Laba Bersih Perusahaan (EAT) - Prasetiyo, Yudhi (UMSurabaya Publishing, 2025)
The latest developments in the climate change crisis, the impact of environmental damage, social welfare mobility, and good governance have forced several companies to adopt new assessment indicators. By maintaining business sustainability or sustainable development in business and industry development based on three important aspects, namely ESG (Environment, Social and Governance) which are formed in the company's sustainability report. This study is a quantitative study with an exploratory approach by looking at the results of the Company's financial performance and the sustainability reports it produces. The sample in this study is an Energy Company listed on the Indonesian Stock Exchange in the 2021-2022 period. Testing uses statistics with SEM PLS analysis. The results of the study show that environmental indicators have a significant influence on the profitability that the company will obtain, while social and governance indicators do not have a significant influence on the company's profitability